DESIGNING DRUG REHABILITATION WITH BIOPHILIC ARCHITECTURE APPROACH IN MEDAN CITY - Rahman, Vinky; Sipayung, Desvita Angelia (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Rehabilitation is the restoration of mental and physical health aimed at drug addicts who have undergone a curative program. The goal is that addicts do not use illegal drugs anymore and are free from diseases such as physical damage (nerves, brain, lungs, kidneys, liver, and others), mental damage, changes in character from positive to negative, antisocial, diseases such as HIV / AIDS, hepatitis, syphilis, and others due to former drug use. (Subagyo 2006:105). According to the National Narcotics Agency, Drug Rehabilitation is a section devoted to rehabilitating victims of drug abuse. The rehabilitation center for victims of drug abuse is tasked with handling patients or victims of drug addicts so that treatment is carried out and restoring public health from using or being dependent on drug drugs (BNN, 2021). Drug Rehabilitation has the concept of Biophilic Architecture, which aims to translate the understanding of biophilia to the design of the built environment so that a beneficial relationship between humans and nature in buildings can be realized.